2019
DOI: 10.1136/medhum-2018-011597
|View full text |Cite
|
Sign up to set email alerts
|

The imaginary of precision public health

Abstract: In recent years, precision medicine has emerged as a charismatic name for a growing movement to revolutionise biomedicine by bringing genomic knowledge and sequencing to clinical care. Increasingly, the precision revolution has also included a new paradigm called precision public health—part genomics, part informatics, part public health and part biomedicine. Advocates of precision public health, such as Sue Desmond-Hellmann, argue that adopting cutting-edge big data approaches will allow public health actors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, this population-centered model of genomic healthcare delivery has been criticized [37] as being a salvage attempt to rescue something of value from the numerous extremely expensive genome projects that had been the scientific rage of the late 20th and early 21st centuries. Reardon and others [37,53,54] claim PPH is most likely dangerous fantasy, exacerbating global economic differences, taking the "public" out of "public health," and shifting responsibility for health onto the individual citizen [55,56]. PPH has also been criticized for not recognizing the contributions of the symbiotic microbial genomes [38].…”
Section: Precision Public Healthmentioning
confidence: 99%
“…However, this population-centered model of genomic healthcare delivery has been criticized [37] as being a salvage attempt to rescue something of value from the numerous extremely expensive genome projects that had been the scientific rage of the late 20th and early 21st centuries. Reardon and others [37,53,54] claim PPH is most likely dangerous fantasy, exacerbating global economic differences, taking the "public" out of "public health," and shifting responsibility for health onto the individual citizen [55,56]. PPH has also been criticized for not recognizing the contributions of the symbiotic microbial genomes [38].…”
Section: Precision Public Healthmentioning
confidence: 99%
“…What is new is the modern landscape of health information. Challenges presented by the unprecedented amount and complexity of data include: i) technical difficulties accessing, integrating and sharing health information across multiple domains [60,61] and modalities [62]; ii) ethical [63] and epistemological concerns [64][65][66]; iii) implications of data inaccuracies and selective measurement in routinely collected data [67,68]; and iv) a growing potential for spurious correlations in large datasets [55,65,69]. In turn, a strong foundation in surveillance and descriptive epidemiology is needed to establish an iterative process for interpreting what we know and what we don't know from within and across scientific disciplines (and public health sectors) [55].…”
Section: Ojphimentioning
confidence: 99%
“…Not everyone is keen on the idea of merging public health with concepts borrowed from precision medicine, especially when genomics is involved [63,[98][99][100]. The utility of Precision Public Health has been questioned because its goals and strategies are not fundamentally different from those of traditional public health [101].…”
Section: Promises and Pitfalls Of Precision Public Healthmentioning
confidence: 99%
“…While a consensus appears to be emerging around the concept of PPH, the topic is not without controversy, which has led some junior investigators to argue for the importance of continuing research in this area [12]. Most notably, some have suggested that PPH could divert attention away from the broader determinants of health towards clinical concepts, which tend to be measured with greater accuracy [13]. For example, the social determinants of health, such as social status, are generally not measured well, so they may play a limited role in characterizing populations and identifying optimal interventions [7,14].…”
Section: Precision Public Healthmentioning
confidence: 99%